ENT600: JGE Engineering Sdn Bhd / Aaina Afrina Abd Manaf … [et al.] - Abd Manaf, Aaina Afrina; Abdul Razak, Abdul Halim; Baharum, Muhammad Asri; Hashim, Nur Ashikin; Mohd Isa, Nurul Athira (2018)
JGE Engineering Sdn Bhd focusing on providing engineering services, valve, instrumentation solutions and process control system towards cleaner environment and better future. Established on 2010, JGE Engineering Sdn Bhd begin their business as supplier for valve and instrumentation. After years of experiences, this company widen their skills by offering turnkey engineering solution for clients from various industries. JGE Engineering was endorsed by Department of Environment (DOE) as CEMS consultant which giving them the opportunities to provide turnkey solution to CEMS application ranging from Power Plant, Chemical Plant, and Refineries to Waste Incinerator. Despite of small company, they are committed in delivering their services to meet their clients' needs.